THERE IS MOTIVATION AND ABILITY OF NURSES IN PERFORMANCE IMPROVEMENT AT ROYAL PRIMA GENERAL HOSPITAL MEDAN - Batara Sanjaya Harahap; Ermi Girsang; Ali Napiah Nasution (Jurnal Ekonomi, 2022)
At present, in an effort to improve the quality of hospitals in achieving the goals set by the hospital, qualified nurses are needed. The good performance of qualified nurses influences several factors that affect nurse performance. The results showed that work motivation had a significant direct effect on nurse performance, job satisfaction also had a direct effect on nurse performance, and attitudes towards the profession had an effect on nurse performance. In addition, work motivation and attitudes toward the nursing profession have been shown to have a direct effect on job satisfaction. Based on the findings above, it can be concluded that the variation that occurs in the nurse's performance variable is directly influenced by work motivation, job satisfaction, and attitude towards the profession.